Водогосподарська освоєність території Волинської області - Лажнік, Володимир; Майстер, Андрій; Lazhnik, Volodymyr; Maіster, Andrіі (My University, 2016)
Розглянуто територіальні особливості водогосподарського розвитку Волинської області. Здійснено аналіз основних показників водокористування в області. Визначено суть понять «водогосподарське освоєння території» та «рівень водогосподарської освоєності території». Розраховано агрегований індекс рівня водогосподарської освоєності території адміністративних одиниць області. Проведено групування адміністративних одиниць області за величиною агрегованого індексу рівня водогосподарської освоєності території. Проаналізовано особливості геопросторової диференціації водогосподарської освоєності території регіону. The article deals with the territorial features of water economy development of Volyn region. The analysis of main indicators of water use in the region has been made. The concepts «water economy development of territory» and «water economy development level of territory» have been determined. The aggregated index of water economy development level of administrative units of territory of region has been calculated. Grouping of administrative units according to the quantity integral index of water economy development level of territory has been made. The features of geospatial differentiation of the water economy development of region territory have been analyzed.
Water Economy Development of Territory of Volyn Region
Keywords: територія; водогосподарська освоєність; рівень освоєності території; водні ресурси; Волинська область; territory; water economy development; development level of territory; water resources; Volyn region